Outcomes and Complications of Tibial Tubercle Fractures in Pediatric Patients: A Systematic Review of the Literature. Issue 5 (July 2016) - Pretell-Mazzini, Juan; Kelly, Derek M.; Sawyer, Jeffrey R.; Esteban, Eva M.A.; Spence, David D.; Warner, William C.; Beaty, James H.
Abstract : Background: Systematic review of the literature was done to determine (1) the frequency and type of associated injuries, (2) frequency of concomitant Osgood-Schlatter disease, (3) methods of treatment, (4) functional and radiologic outcomes according to fracture type, and (5) complications of tibial tubercle fractures in pediatric patients. Methods: A systematic review of the English literature from 1970 to 2013 included 23 eligible articles reporting 336 fractures with a mean follow-up of 33.56 months (range, 5.7 to 115 mo). Fractures were classified by a comprehensive system that included characteristics of previous systems. Clinical outcomes were assessed by a qualitative scale (excellent/fair/poor), the rate of return to preinjury activity, and knee range of motion. Rate of fracture healing, associated injuries (patellar/quadriceps tendon avulsion and meniscal tears), compartment syndrome, and complications were also recorded. Results: Mean age at surgery was 14.6 years and the most common fracture reported was type III (50.6%). The overall associated injury rate was 4.1%, most common in type III fractures (4.7%). Compartment syndrome was present in 3.57% of cases. Open reduction and internal fixation were done in 98% of surgical cases. Rates of return to preinjury activity and knee range of motion were 98%, regardless of the type of fracture. Fracture consolidation was achieved in 99.4% of cases. Overall complication rate was 28.3%; removal of an implant because of bursitis (55.8%) was most common. Tenderness/prominence (17.9%) and refracture (6.3%) were also common. Conclusions: Treatment of tibial tubercle fractures in adolescents produced good clinical and radiologic results regardless of fracture type, which was more related to potential complications. Fractures with intra-articular involvement tended to present with more associated injuries and to have fair functional outcomes, suggesting that advanced imaging may be justified with these fractures. Complications could be more common than expected without a significant effect on final outcome. Finally, there is a need for longer follow-up to determine long-term outcomes. Level of Evidence: Level III—systematic review of level III/IV studies.